Modified MR scoring system for assessment of sonographically indeterminate ovarian and adnexal masses in the absence of dynamic contrast-enhanced - Moradi, Behnaz; Rahmani, Maryam; Aghasi, Maryam; Yarandi, Fariba; Malek, Mahrooz; Hosseini, Ashrafsadat; Ghafouri, Kimia; Hasan Zadeh Tabatabaei, Mahgol Sadat; Shirali, Elham; Riahi Samani, Payam; Firouznia, Sina (British journal of radiology, 2024)
OBJECTIVES: Dynamic contrast-enhanced (DCE) MRI is not available in all imaging centres to investigate adnexal masses. We proposed modified magnetic resonance (MR) scoring system based on an assessment of the enhancement of the solid tissue on early phase postcontrast series and diffusion-weighted imaging (DWI) with apparent diffusion coefficient (ADC) map and investigated the validity of this protocols in the current study. MATERIALS AND METHODS: In this cross-sectional retrospective study, pelvic MRI of a total of 245 patients with 340 adnexal masses were studied based on the proposed modified scoring system and ADNEX MR scoring system. RESULTS: Modified scoring system with the sensitivity of 87.3% and specificity of 94.6% has an accuracy of 92.1%. Sensitivity, specificity, and accuracy of ADNEX MR scoring system is 96.6%, 91%, and 92.9%, respectively. The area under the receiver operating characteristic curve for the modified scoring system and ADNEX MR scoring system is 0.909 (with 0.870-0.938 95% confidence interval [CI]) and 0.938 (with 0.907-0.961 95% CI), respectively. Pairwise comparison of these area under the curves showed no significant difference (P = .053). CONCLUSIONS: Modified scoring system is less sensitive than the ADNEX MR scoring system and more specific but the accuracy is not significantly different. ADVANCES IN KNOWLEDGE: According to our study, MR scoring system based on subjective assessment of the enhancement of the solid tissue on early phase postcontrast series and DWI with ADC map could be applicable in imaging centres that DCE is not available.
Keywords: ovarium; Magnetic Resonance Imaging; Cross-Sectional Studies; Female; retrospektivní studie; magnetická rezonanční tomografie; Ovary; Humans; ženské pohlaví; Magnetic Resonance Spectroscopy; lidé; Retrospective Studies; magnetická rezonanční spektroskopie; průřezové studie